Análisis de rentabilidad de alternativas de producción de ganado de leche en Duitama (2013)
The purpose of this investigation was to determine if the productive alternatives for mitigation and adaptation to excesses and deficits of rainfall present a high probability of profitability for the specialized milk producers of Duitama. To achieve this objective, the El Niño and La Niña phenomena were analyzed, detailing what they are and when a phenomenon of this type occurs. Likewise, the climate of Duitama was characterized and analyzed with data obtained from the IDEAM, from where a probability distribution of the monthly precipitations was obtained, to later use those distributions in order to collect the effect of the climate on the production of pastures, oats and corn.